Ultra-weatherable wood grain paper white ink color paste and preparation method thereof

CN122427558BActive Publication Date: 2026-10-27YINGDE KEDI PIGMENT TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610714880.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-05-22
Publication Date
2026-10-27
Estimated Expiration
2046-05-22

AI Technical Summary

Technical Problem

有研究采用氧化铝包覆钛白粉,但其包覆层致密性不足,光催化活性抑制效果有限

Benefits of technology

本发明提供的色浆,采用的成膜树脂是超支化聚氧硅烷改性的二氧化碳基聚氨酯丙烯酸杂化树脂,采用的颜料为依次经过二氧化硅、硅烷偶联剂和聚合物改性的改性钛白粉,且成膜树脂与改性钛白粉之间具有优异的相容性,使得由改性聚氨酯丙烯酸杂化树脂、改性钛白粉与其他助剂进行复配而得的色浆,具有优异的耐候性、耐摩擦色牢度、附着力、耐热压性,综合性能优异,可作为木纹纸白墨色浆使用,具有极强的工业应用价值。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a kind of super weather-resistant wood grain paper white ink color paste and preparation method thereof, the color paste includes: modified polyurethane acrylic hybrid resin, modified titanium dioxide, adhesion promoter, leveling agent, ultraviolet absorber, hindered amine light stabilizer, crosslinking agent, hydrolysis inhibitor, defoaming agent, 1,3-propanediol, deionized water.The color paste provided by the application uses super-branched polyoxysilane modified carbon dioxide-based polyurethane acrylic hybrid resin as film-forming resin, uses modified titanium dioxide modified by silicon dioxide, silane coupling agent and polymer in turn as pigment, and the film-forming resin and modified titanium dioxide have excellent compatibility, so that the color paste obtained by compounding modified polyurethane acrylic hybrid resin, modified titanium dioxide and other additives has excellent weather resistance, rubbing fastness, adhesion, heat resistance and excellent comprehensive performance, and can be used as wood grain paper white ink color paste.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a white ink paste for ultra-weather-resistant wood grain paper and its preparation method, belonging to the field of ink paste technology. Background Technology

[0002] Wood grain paper is widely used in furniture decoration, flooring, doors and windows, etc. To extend its outdoor service life, a special weather-resistant white ink paste is often applied to the surface of wood grain paper. Titanium dioxide is a functional powder material with submicron-sized crystalline titanium dioxide as its main component. It has advantages such as high refractive index, strong hiding and tinting power, and good weather resistance. Currently, it is widely used as a pigment in weather-resistant white ink pastes. However, titanium dioxide exhibits photocatalytic activity under ultraviolet light irradiation, leading to degradation, pulverization, and yellowing of the resin base and wood grain paper substrate, seriously affecting the weather resistance and service life of the ink paste. In addition, titanium dioxide is prone to agglomeration and poor dispersibility in the ink paste, further deteriorating the ink paste performance. Therefore, it is necessary to perform surface modification treatment on titanium dioxide.

[0003] Current technologies primarily employ inorganic surface coatings to modify titanium dioxide. Some studies have used alumina to coat titanium dioxide, but the coating layer lacks sufficient density, resulting in limited photocatalytic activity inhibition. Other studies have used silica to coat titanium dioxide, but insufficient compatibility between the coating layer and the film-forming resin of the pigment paste leads to inadequate modification. Furthermore, some studies have used organic polymers or silane coupling agents to coat or surface-modify titanium dioxide; however, the compatibility of organic polymers and silane coupling agents with the film-forming resin of the pigment paste remains insufficient, resulting in limited modification effects on the pigment paste. Summary of the Invention

[0004] To address the aforementioned problems in the existing technology, the purpose of this invention is to provide a super weather-resistant wood grain paper white ink paste and its preparation method.

[0005] To achieve the above objectives, the present invention adopts the following technical solution: A super weather-resistant wood grain paper white ink paste has the following composition and proportions: Modified polyurethane acrylic hybrid resin: 40-50 parts by weight; Modified titanium dioxide: 15-25 parts by weight; Adhesion promoter: 0.5-1.0 parts by weight; Leveling agent: 0.2-0.4 parts by weight; Ultraviolet absorber: 1.0-2.0 parts by weight; Hindered amine light stabilizer: 1.0-2.0 parts by weight; Crosslinking agent: 3-5 parts by weight; Anti-hydrolysis agent: 0.5-1.0 parts by weight; Defoamer: 0.2-0.4 parts by weight; 1,3-Propanediol: 5-8 parts by weight; Deionized water: 35-45 parts by weight; The modified polyurethane-acrylate hybrid resin is obtained by first reacting polypropylene carbonate diol (PPCD, Mn=1000), isophorone diisocyanate (IPDI), dimethylolpropionic acid (DMPA), and hydroxypropyl acrylate (HPA) to obtain a polyurethane prepolymer, and then copolymerizing the polyurethane prepolymer with methyl methacrylate (MMA), butyl acrylate (BA), isobornyl acrylate (IBOA), and hyperbranched polyoxysilane (F-HBPS). The modified titanium dioxide is first coated with a silicon dioxide layer to obtain SiO2@TiO2 particles. Then, the SiO2@TiO2 particles are surface activated using a silane coupling agent to obtain activated SiO2@TiO2 particles. Then, hyperbranched polyoxysilane (F-HBPS), methyl methacrylate (MMA), and butyl acrylate (BA) are grafted and copolymerized onto the surface of the activated SiO2@TiO2 particles to form a copolymer layer. The hyperbranched polyoxysilane is obtained by co-hydrolysis and polycondensation reaction of γ-glycidoxypropyltrimethoxysilane (KH560), γ-methacryloyloxypropyltrimethoxysilane (KH570) and diethylene glycol (DEG).

[0006] In one embodiment, the mass ratio of polypropylene carbonate diol: isophorone diisocyanate: dimethylolpropionic acid: hydroxypropyl acrylate: methyl methacrylate: butyl acrylate: isobornyl acrylate: hyperbranched polyoxysilane in the modified polyurethane acrylic hybrid resin is 20-25: 8-12: 1-2: 2-3: 12-18: 6-10: 3-6: 2-4.

[0007] In a preferred embodiment, the preparation of the modified polyurethane-acrylic hybrid resin includes the following steps: 1) Add polypropylene carbonate diol (Mn=1000), isophorone diisocyanate (IPDI), dimethylolpropionic acid (DMPA), and catalyst to a reactor and react at 85-90℃ for 2-3 hours under nitrogen protection; then cool to 60℃ and add hydroxypropyl acrylate (HPA) for end-capping for 1.5-2 hours; then cool to 40℃ and add an appropriate amount of triethylamine to neutralize to pH=7.0-8.0; then add deionized water under high-speed stirring and emulsify for 20-30 minutes to obtain a polyurethane prepolymer emulsion (solid content approximately 30%). 2) Heat the polyurethane prepolymer emulsion to 75-80℃, and under nitrogen protection, slowly add a mixture of methyl methacrylate (MMA), butyl acrylate (BA), isobornyl acrylate (IBOA), hyperbranched polyoxysilane (F-HBPS) and initiator. The addition time is 2-3 hours. After the addition is completed, continue to keep the temperature and react for another 2-3 hours to obtain the modified polyurethane acrylic hybrid resin.

[0008] In a preferred embodiment, in step 1), the catalyst is at least one of dibutyltin dilaurate (DBTDL), zinc isooctanoate, and bismuth catalyst (e.g., K-KAT 348), with DBTDL being preferred; the mass ratio of polypropylene carbonate diol: isophorone diisocyanate: dimethylolpropionic acid: catalyst: hydroxypropyl acrylate: deionized water is 20-25: 8-12: 1-2: 0.02-0.05: 2-3: 40-50.

[0009] In a preferred embodiment, in step 2), the initiator is at least one of azobisisobutyronitrile (AIBN), azobisisobutyronitrile (ABVN), and benzoyl peroxide (BPO); the mass ratio of methyl methacrylate: butyl acrylate: isobornyl acrylate: hyperbranched polyoxysilane: initiator is 12-18: 6-10: 3-6: 2-4: 0.3-0.5.

[0010] One embodiment of the modified titanium dioxide includes the following steps: ①Preparation of SiO2@TiO2 particles: Disperse rutile titanium dioxide (e.g., R-996) in deionized water, add sodium hexametaphosphate, adjust the pH to 9.0-10.0 with NaOH aqueous solution (concentration 5-15wt%), then heat to 85-95℃, slowly add sodium silicate aqueous solution (concentration 5-10wt%), and simultaneously add dilute sulfuric acid (concentration 5-15wt%), maintaining pH=9.0-10.0, adding for 1.5-2 hours. After the addition is completed, keep warm for 1-3 hours, filter, wash, and dry to obtain SiO2@TiO2 particles; ② Surface activation: Disperse SiO2@TiO2 particles in an ethanol-water solution (ethanol to water volume ratio of 1:1), adjust the pH to 4-5 with glacial acetic acid, add silane coupling agent, react at 60-70℃ for 2-3 hours, filter, wash and dry to obtain activated SiO2@TiO2 particles; ③Graft copolymerization: Activated SiO2@TiO2 particles are dispersed in an appropriate amount of ethanol-water solution (ethanol to water volume ratio of 1:1), hyperbranched polyoxysilane, methyl methacrylate, butyl acrylate and initiator are added, and the reaction is carried out at 75-80℃ under nitrogen protection for 3-5 hours. After filtration, washing and drying (60℃ vacuum), the particles are pulverized and sieved (through a 325-mesh sieve) to obtain modified titanium dioxide.

[0011] In a preferred embodiment, in step ①, the mass ratio of titanium dioxide: sodium hexametaphosphate: sodium silicate is 100:0.2-0.5:20-30, and when dispersing titanium dioxide, the amount of deionized water added is 3-4 times the mass of titanium dioxide.

[0012] In a preferred embodiment, in step ②, the mass ratio of SiO2@TiO2 particles to silane coupling agent is 100:2-5, the silane coupling agent is KH-570, and the amount of ethanol aqueous solution added is 1-3 times that of SiO2@TiO2 particles.

[0013] In a preferred embodiment, in step ③, the mass ratio of activated SiO2@TiO2 particles: hyperbranched polyoxysilane: methyl methacrylate: butyl acrylate: initiator is 100:3-8:5-10:3-5:0.1-0.3; the initiator is azobisisobutyronitrile (AIBN).

[0014] In one embodiment, the mass ratio of γ-glycidoxypropyltrimethoxysilane:γ-methacryloyloxypropyltrimethoxysilane:diethylene glycol in the hyperbranched polyoxysilane is 22-28:12-20:10-18.

[0015] In a preferred embodiment, the preparation of the hyperbranched polyoxysilane includes the following steps: γ-glycidoxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, diethylene glycol, ethanol and water were mixed, and the pH was adjusted to 3-4 with dilute hydrochloric acid. The mixture was hydrolyzed at 50-60℃ for 0.5-1.5 hours. Then the temperature was raised to 75-85℃ and the polycondensation reaction was carried out for 3-4 hours. After the reaction was completed, the mixture was distilled under reduced pressure to obtain hyperbranched polyoxysilane.

[0016] In a preferred embodiment, during the preparation of hyperbranched polyoxysilane, the mass ratio of γ-glycidoxypropyltrimethoxysilane:γ-methacryloyloxypropyltrimethoxysilane:diethylene glycol:ethanol:water is 22-28:12-20:10-18:6-12:25-40.

[0017] In one embodiment, the adhesion promoter is γ-aminopropyltriethoxysilane (KH-550); the leveling agent is an acrylate leveling agent, for example, BYK-381; the ultraviolet absorber is 2-hydroxy-4-(2-hydroxyethoxy)benzotriazole; the hindered amine light stabilizer is 2,2,6,6-tetramethylpiperidin methacrylate; the crosslinking agent is a blocked isocyanate crosslinking agent, specifically a blocked HDI trimer, for example, ZS-2601 from Guangzhou Zengmao Chemical Technology Co., Ltd., or YL-WB9500 from Guangdong Yele New Material Manufacturing Co., Ltd.; the anti-hydrolysis agent is carbodiimide; and the defoamer is a polyether-modified silicone defoamer, for example, BD-3062 from Hangzhou Baode New Material Technology Co., Ltd., or BYK-024 and BYK-028 from BYK Chemical.

[0018] A method for preparing white ink paste for ultra-weather-resistant wood grain paper includes the following steps: a) Mix deionized water, 1,3-propanediol, adhesion promoter, leveling agent, defoamer, UV absorber, and hindered amine light stabilizer evenly. b) Add modified titanium dioxide and stir to mix evenly. Add the resulting mixture to a grinder and use zirconium dioxide as the grinding media to grind the mixture. After grinding, separate the resulting grinding solution from the zirconium beads. c) Add the modified polyurethane-acrylic hybrid resin and stir until it is evenly mixed; then add the crosslinking agent and anti-hydrolysis agent, stir until it is evenly mixed, filter and discharge to obtain the ultra-weather-resistant wood grain paper white ink paste.

[0019] Compared with the prior art, the present invention has the following significant advantages: The color paste provided by this invention uses a hyperbranched polyoxysilane-modified carbon dioxide-based polyurethane-acrylic hybrid resin as the film-forming resin and a modified titanium dioxide pigment that has been sequentially modified with silica, silane coupling agent, and polymer. The film-forming resin and the modified titanium dioxide have excellent compatibility, resulting in a color paste obtained by compounding the modified polyurethane-acrylic hybrid resin, modified titanium dioxide, and other additives. This color paste has excellent weather resistance, rubbing fastness, adhesion, and heat-pressing resistance, exhibiting superior overall performance. It can be used as a white ink color paste for wood grain paper and has extremely high industrial application value. Detailed Implementation

[0020] The technical solution of the present invention will be further described in detail and completely below with reference to the embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. Experimental methods in the following embodiments that do not specify specific conditions are generally performed under conventional conditions or as recommended by the manufacturer. Example 1

[0021] 1) Preparation of hyperbranched polyoxysilanes 25 parts by mass of γ-glycidyl etheroxypropyltrimethoxysilane (KH560, Nanjing Chenggong Organosilicon Materials Co., Ltd.), 16 parts by mass of γ-methacryloyloxypropyltrimethoxysilane (KH570, Nanjing Chenggong Organosilicon Materials Co., Ltd.), 14 parts by mass of diethylene glycol (DEG, Sinopharm Chemical Reagent Co., Ltd.), 9 parts by mass of ethanol and 32 parts by mass of deionized water were added to a reaction vessel. The pH was adjusted to 3.5 with dilute hydrochloric acid (10 wt%), and hydrolysis was carried out at 55 °C for 1 hour. Then the temperature was raised to 80 °C, and the polycondensation reaction was carried out for 3.5 hours. After the reaction was completed, the low-boiling substances were removed by vacuum distillation at 70 °C and 0.095 MPa to obtain hyperbranched polyoxysilane (denoted as F-HBPS-1).

[0022] (ii) Preparation of modified polyurethane acrylic hybrid resin 1) 22 parts by weight of polypropylene carbonate diol (PPCD, Mn=1000, Jiangsu Zhongke Jinlong Chemical Co., Ltd.), 10 parts by weight of isophorone diisocyanate (IPDI, Evonik Industries AG, Germany), 1.5 parts by weight of dimethylolpropionic acid (DMPA, Shanghai Aladdin Biochemical Technology Co., Ltd.), and 0.02 parts by weight of dibutyltin dilaurate (DBTDL, Shanghai Maclean Biochemical Technology Co., Ltd.) were added to a reactor. The mixture was heated to 85°C under nitrogen protection and stirred for 2.5 hours. The temperature was then lowered to 60°C, and 2.5 parts by weight of hydroxypropyl acrylate (HPA, Shanghai Titan Technology Co., Ltd.) were added for end-capping for 1.5 hours. The temperature was then lowered to 40°C, and 1.2 parts by weight of triethylamine (TEA, Sinopharm Chemical Reagent Co., Ltd.) were added to neutralize to pH=7.5. 45 parts by weight of deionized water were slowly added under high-speed stirring, and the mixture was emulsified for 25 minutes to obtain a polyurethane prepolymer emulsion with a solid content of approximately 30%. 2) The above polyurethane prepolymer emulsion was heated to 78°C, and under nitrogen protection, a mixture consisting of 15 parts by mass of methyl methacrylate (MMA, Shanghai Titan Technology Co., Ltd.), 8 parts by mass of butyl acrylate (BA, Shanghai Titan Technology Co., Ltd.), 5 parts by mass of isobornyl acrylate (IBOA, Shanghai Guangyi Chemical Co., Ltd.), 3 parts by mass of hyperbranched polyoxysilane F-HBPS-1, and 0.4 parts by mass of azobisisobutyronitrile (AIBN, Shanghai Aladdin Biochemical Technology Co., Ltd.) was slowly added dropwise over 2.5 hours. After the addition was completed, the reaction was continued at the temperature for another 2.5 hours. After cooling and filtration, the modified polyurethane acrylic hybrid resin (denoted as resin A-1) was obtained.

[0023] (iii) Preparation of modified titanium dioxide ①Preparation of SiO2@TiO2 particles: 100 parts by weight of rutile titanium dioxide (R-996, Sichuan Longmang Group) were dispersed in 300 parts by weight of deionized water. 0.3 parts by weight of sodium hexametaphosphate (Sinopharm Chemical Reagent Co., Ltd.) were added. The pH was adjusted to 9.5 with 10wt% NaOH aqueous solution. Then the temperature was raised to 90℃, and sodium silicate aqueous solution (prepared by 20 parts by weight of sodium silicate + 100 parts by weight of deionized water) was slowly added dropwise. During the dropwise addition, 10wt% dilute sulfuric acid was added dropwise to maintain the pH = 9.0-10.0. The dropwise addition time was 1.5 hours. After the dropwise addition was completed, the mixture was kept at the temperature for 2 hours for aging. After filtration, the mixture was washed with deionized water until the conductivity was <500μS / cm. The mixture was dried at 105℃ for 12 hours to obtain SiO2@TiO2 particles. ② Surface activation: 100 parts by mass of SiO2@TiO2 particles were dispersed in 200 parts by mass of ethanol / water mixture (volume ratio 1:1), the pH was adjusted to 4.5 with glacial acetic acid, 3 parts by mass of silane coupling agent KH-570 (Nanjing Chenggong Organosilicon Materials Co., Ltd.) were added, and the reaction was carried out at 65℃ for 2.5 hours. After filtration, the particles were washed twice with ethanol and dried under vacuum at 60℃ to obtain activated SiO2@TiO2 particles. ③ Graft copolymerization: 100 parts by mass of activated SiO2@TiO2 particles were dispersed in 200 parts by mass of an ethanol / water mixture (volume ratio 1:1). 5 parts by mass of hyperbranched polyoxysilane F-HBPS-1, 8 parts by mass of methyl methacrylate (MMA, Shanghai Titan Technology Co., Ltd.), 4 parts by mass of butyl acrylate (BA, Shanghai Titan Technology Co., Ltd.), and 0.2 parts by mass of azobisisobutyronitrile (AIBN, Shanghai Aladdin Biochemical Technology Co., Ltd.) were added. The mixture was reacted at 78°C under nitrogen protection for 4 hours, filtered, washed three times with ethanol, and vacuum dried at 60°C for 24 hours. The mixture was then lightly dispersed using an air jet mill and passed through a 325-mesh sieve (pore size 45μm) to obtain modified titanium dioxide (denoted as titanium dioxide M-1).

[0024] (iv) Preparation of white ink paste for wood grain paper a) Add 40 parts by weight of deionized water, 6 parts by weight of 1,3-propanediol (Sinopharm Chemical Reagent Co., Ltd.), 0.8 parts by weight of adhesion promoter (γ-aminopropyltriethoxysilane KH-550, Nanjing Chenggong Organosilicon Materials Co., Ltd.), 0.3 parts by weight of acrylate leveling agent (BYK-381, BYK Chemicals, Germany), 0.3 parts by weight of polyether modified organosilicon defoamer (BD-3062, Hangzhou Baode New Material Technology Co., Ltd.), 1.5 parts by weight of ultraviolet absorber (2-hydroxy-4-(2-hydroxyethoxy)benzotriazole, Tianjin Xiens Biochemical Technology Co., Ltd.), and 1.5 parts by weight of hindered amine light stabilizer (2,2,6,6-tetramethylpiperidin methacrylate, Shanghai Maclean Biochemical Technology Co., Ltd.) to a dispersion tank and stir at 1500 rpm for 20 minutes until homogeneous. b) Add 20 parts by weight of modified titanium dioxide M-1 and stir at 2000 rpm for 30 minutes to fully wet and disperse the titanium dioxide; add the resulting mixture to a sand mill and grind at 2800 rpm for 1.5 hours using zirconium dioxide beads (0.3-0.5 mm) until the particle size D50 < 200 nm. After grinding, separate the resulting grinding solution from the zirconium beads. c) Add 45 parts by weight of modified polyurethane acrylic hybrid resin A-1 and stir at 800 rpm for 20 minutes; then add 4 parts by weight of crosslinking agent (blocked HDI trimer YL-WB9500, Guangdong Yele New Material Manufacturing Co., Ltd.) and 0.8 parts by weight of anti-hydrolysis agent (carbodiimide, Shanghai Langyi Biotechnology Co., Ltd.), and stir at 500 rpm for 10 minutes; finally, filter through a 1.0 μm filter to obtain ultra-weather-resistant wood grain paper white ink paste (denoted as S-1). Example 2

[0025] The difference between this embodiment and Example 1 is that the content of each component in the color paste formulation is different. The specific formulation is as follows: 40 parts by weight of modified polyurethane acrylic hybrid resin A-1, 25 parts by weight of modified titanium dioxide M-1, 1.0 part by weight of KH-550, 0.4 parts by weight of BYK-381, 2.0 parts by weight of ultraviolet absorber, 2.0 parts by weight of hindered amine light stabilizer, 5 parts by weight of YL-WB9500, 1.0 part by weight of carbodiimide, 0.4 parts by weight of BD-3062, 8 parts by weight of 1,3-propanediol, and 45 parts by weight of deionized water. The rest is the same as in Example 1, resulting in color paste S-2. Example 3

[0026] The difference between this embodiment and Example 1 is that the content of each component in the color paste formulation is different. The specific formulation is as follows: 50 parts by weight of modified polyurethane acrylic hybrid resin A-1, 15 parts by weight of modified titanium dioxide M-1, 0.5 parts by weight of KH-550, 0.2 parts by weight of BYK-381, 1.0 part by weight of ultraviolet absorber, 1.0 part by weight of hindered amine light stabilizer, 3 parts by weight of YL-WB9500, 0.5 parts by weight of carbodiimide, 0.2 parts by weight of BD-3062, 5 parts by weight of 1,3-propanediol, and 35 parts by weight of deionized water. The rest is the same as in Example 1, resulting in color paste S-3.

[0027] Comparative Example 1 The difference between this comparative example and Example 1 is that the raw materials used in the preparation of the polyurethane-acrylic hybrid resin in the color paste are different. This comparative example does not use carbon dioxide-based PPCD, but instead uses conventional polyether diol (polypropylene glycol PPG-1000, Shandong Lanxing Dongda Chemical Co., Ltd.) instead of PPCD, and does not perform hyperbranched polyoxysilane modification (i.e., does not add hyperbranched polyoxysilane F-HBPS-1). Specifically, the preparation method of the polyurethane-acrylic hybrid resin in this comparative example is as follows: 1) Add 22 parts by weight of PPG-1000, 10 parts by weight of IPDI, 1.5 parts by weight of DMPA and 0.02 parts by weight of DBTDL to a reactor. Under nitrogen protection, heat to 85°C and stir for 2.5 hours. Cool down to 60°C and add 2.5 parts by weight of HPA for end-capping for 1.5 hours. Cool down to 40°C and add 1.2 parts by weight of triethylamine to neutralize to pH=7.5. Slowly add 45 parts by weight of deionized water under high-speed stirring and emulsify for 25 minutes to obtain a polyurethane prepolymer emulsion. 2) The above polyurethane prepolymer emulsion was heated to 78°C, and under nitrogen protection, a mixed monomer (excluding hyperbranched polyoxysilane) consisting of 15 parts by mass of MMA, 8 parts by mass of BA, 5 parts by mass of IBOA and 0.4 parts by mass of AIBN was slowly added dropwise over 2.5 hours. After the addition was completed, the reaction was continued at the temperature for another 2.5 hours to obtain a comparative polyurethane acrylic hybrid resin (denoted as resin A-C1). The rest is the same as in Example 1, to color paste S-C1.

[0028] Comparative Example 2 The difference between this comparative example and Example 1 is that unmodified rutile titanium dioxide (R-996) was used in the color paste instead of the self-made modified titanium dioxide M-1 in Example 1. The rest is the same as in Example 1, and color paste S-C2 is obtained.

[0029] Comparative Example 3 The difference between this comparative example and Example 1 is that the titanium dioxide used in the color paste was only modified by silica coating, without subsequent activation treatment and polymer coating modification. Specifically, the preparation method of the modified titanium dioxide in this comparative example is as follows: 100 parts by weight of rutile titanium dioxide (R-996) were used to prepare SiO2@TiO2 particles using the same method as step ① in Example 1, without performing subsequent steps ② and ③. These SiO2@TiO2 particles were used as a comparative modified titanium dioxide (denoted as titanium dioxide M-C3). The rest is the same as in Example 1, and the color paste S-C3 is obtained.

[0030] Comparative Example 4 The difference between this comparative example and Example 1 is that the titanium dioxide used in the color paste, after being modified by silica coating and activated by coupling agent, does not contain hyperbranched polyoxysilane in the polymer during polymer coating modification. Specifically, the preparation method of the modified titanium dioxide in this comparative example is as follows: Steps ① and ② are exactly the same as in Example 1, obtaining activated SiO2@TiO2 particles; in step ③, during graft copolymerization, 100 parts by mass of activated SiO2@TiO2 particles are dispersed in 200 parts by mass of ethanol / water mixture, and 8 parts by mass of MMA, 4 parts by mass of BA and 0.2 parts by mass of AIBN (without adding hyperbranched polyoxysilane F-HBPS-1) are added. The reaction is carried out at 78°C under nitrogen protection for 4 hours, and the post-treatment is the same as in Example 1, obtaining the comparative modified titanium dioxide (denoted as titanium dioxide M-C4). The rest is the same as in Example 1, and the color paste S-C4 is obtained.

[0031] Comparative Example 5 The difference between this comparative example and Example 1 is that the color paste does not contain adhesion promoter (KH-550), crosslinking agent (YL-WB9500) and anti-hydrolysis agent (carbodiimide), while the rest is the same as in Example 1, resulting in color paste S-C5.

[0032] The color pastes prepared in Examples 1-3 and Comparative Examples 1-5 were uniformly coated onto the surface of melamine-formaldehyde resin impregnated wood grain paper (hereinafter referred to as melamine impregnated paper, commercially available industrial grade product) using a 10μm wire bar coater. The coating area was 10cm × 10cm. The coated sample was placed in a 60℃ oven to dry for 5 minutes, and then cured in a 100℃ oven for 20 minutes (to promote the deblocking and crosslinking of the crosslinking agent). After being removed and cooled to room temperature, a uniform color paste coating was obtained. This coating was used to test weather resistance, rubbing fastness, adhesion, and heat-pressing resistance. Specifically: 1) Adhesion test Referring to GB / T 9286-2021 "Cross-cut Test for Paints and Varnishes", a 10×10 grid (1mm spacing, grid depth penetrating the coating to the substrate) was made on the coating surface using a cross-cut tester. 3M tape (model 610, adhesion strength 4.5N / 25mm) was then applied and vertically peeled off. The coating peeling was observed and rated from 0 to 5: Grade 0: The cut edges are completely smooth, with no grid peeling; Grade 1: A small amount of coating peeling occurs at the intersection of the cuts, with a peeling area ≤5%; Grade 2: Peeling area 5-15%; Grade 3: Peeling area 15-35%; Grade 4: Peeling area 35-65%; Grade 5: Peeling area >65%. 2) Color fastness to rubbing test Referring to GB / T 3920-2008 "Textiles - Tests for color fastness to rubbing", a rubbing fastness tester (Y571C type) was used. The coated sample was fixed on the test table, and a black standard rubbing cloth (cotton, size 50mm×50mm, conforming to GB / T 7568.2-2008) was rubbed 50 times under a load of 500g. After the rubbing was completed, a standard gray scale for staining (GB / T 251-2008) was taken, and the degree of staining of the black standard rubbing cloth was compared with the naked eye or a colorimeter. The results were rated from 1 to 5: 5 is no staining, 4 is slight staining, 3 is obvious staining, 2 is relatively heavy staining, and 1 is severe staining. 3) Weathering resistance test (QUV accelerated aging) Referring to GB / T 23987-2009 "Artificial Climate Aging of Paint and Varnish Coatings - Exposure to Fluorescent UV Lamp and Water", an accelerated aging tester (Q-Lab) was used with a UV-B lamp (313nm, irradiance 0.63W / m²). The test conditions were: 60℃ for 4 hours during the illumination phase and 50℃ for 4 hours during the condensation phase, alternating between the two phases, for a total test time of 1000 hours. After the test, the color difference ΔE of the coating before and after aging was measured using a colorimeter (Konica Minolta CM-5), and the gloss at a 60° angle of the coating before and after aging was measured using a gloss meter (BYK 4563). The gloss retention rate (%) was calculated. 4) Heat and pressure resistance test In accordance with the relevant requirements of GB / T 15102-2017 "Impregnated Paper-faced Artificial Boards", wood grain paper coated with colored paste was stacked with uncoated melamine-impregnated paper and placed in a hot press. The hot pressing conditions were: temperature 180±5℃, pressure 10±1MPa, and time 60 seconds. After hot pressing, the sample was removed and cooled to room temperature. The yellowing index of the coating before and after hot pressing was measured using a colorimeter, and the yellowing index ΔYI was calculated according to ASTM E313 standard. The adhesion grade of the coating after hot pressing was tested according to GB / T 9286-2021 and compared with that before hot pressing. The coating after hot pressing was observed to see if cracking, whitening, blistering, or other phenomena occurred.

[0033] The test results are shown in Table 1.

[0034] Table 1 Performance test data of color pastes from Examples 1-3 and Comparative Examples 1-5

[0035] As shown in Table 1, the color pastes of Examples 1-3 of this invention exhibit the following characteristics: adhesion grade 0, indicating extremely strong interfacial bonding with the wood grain paper substrate; dry rubbing color fastness grade 4-5, indicating excellent rubbing color fastness; after 1000 hours of QUV accelerated aging, the color difference ΔE is less than 1.5, and the gloss retention rate is higher than 90%, indicating extremely excellent weather resistance; after high-temperature and high-pressure hot pressing at 180℃, the yellowing index ΔYI is less than 2.0, the adhesion grade remains at 0, and the coating appearance shows no change, indicating excellent heat-pressing resistance. In summary, the color pastes in Examples 1-3 have excellent comprehensive performance and can be used as white ink color pastes for wood grain paper. Furthermore, as can be seen from the table, the color pastes of Examples 1-3 have significantly better overall performance than the color pastes of Comparative Examples 1-5. This may be because: 1) Adhesion: First, in the examples, the modified polyurethane acrylic hybrid resin A-1 uses polypropylene carbonate glycol (PPCD) as the soft segment. Its molecular chain contains highly polar carbonate bonds, which can form strong hydrogen bonds and van der Waals forces with the hydroxyl and amino groups of the melamine resin on the wood grain paper surface. In contrast, in Comparative Example 1, resin A-C1 uses low-polarity polypropylene glycol (PPG-1000) instead of PPCD. Its molecular chain only contains ether bonds, which are weakly polar, resulting in poor adhesion. Furthermore, the color paste in the examples contains the adhesion promoter KH-550 (γ-aminopropyltriethoxysilane), whose silanoxy groups can condense with the silanol groups on the surface of wood grain paper to form strong Si-O-Si covalent bonds, while the amino groups can react with the carboxyl and isocyanate groups in the resin to form "molecular bridges"; however, the color paste in Comparative Example 5 lacks KH-550 and relies solely on physical adsorption, resulting in reduced adhesion. Furthermore, the blocked isocyanate crosslinking agent contained in the color paste of the embodiment releases -NCO after deblocking, and reacts with -OH, -COOH in the resin and -NH2 in KH-550 to form a high-density three-dimensional chemical crosslinking network, thereby enhancing the cohesive strength of the coating and its adhesion to the substrate, thus making the color paste of the embodiment have better adhesion. 2) Regarding color fastness to rubbing: The pigment used in the color paste of the embodiment is modified titanium dioxide M-1, which is obtained by triple modification treatment of titanium dioxide coating, silane activation and polymer grafting. The grafted polymer layer is copolymerized from hyperbranched polyoxysilane, MMA and BA. Its chemical composition is highly matched with resin A-1, so that the grafted polymer layer and resin A-1 undergo segment interpenetration and chemical cross-linking during the curing process, which can firmly "anchor" the titanium dioxide particles in the resin matrix and make them less likely to fall off during friction. In contrast, the pigment used in the color paste of Comparative Example 2 is unmodified titanium dioxide. The titanium dioxide and the resin are only physically adsorbed, and the interfacial bonding force is weak. It is easy to detach from the resin matrix when rubbed, which leads to a decrease in its rubbing fastness. The titanium dioxide M-C3 used in the color paste of Comparative Example 3 is only coated with SiO2 layer and has no polymer grafting layer. The SiO2 layer has poor compatibility with the resin and there are micro-defects at the interface. The interface is easy to peel off when rubbed, which leads to a decrease in its rubbing fastness. Although the titanium dioxide M-C4 used in the color paste of Comparative Example 4 also underwent triple modification treatment of silica coating, silane activation, and polymer grafting, the grafted polymer layer did not contain hyperbranched polyoxysilane, which prevented it from achieving molecular-level interpenetration and entanglement with resin A-1, thus limiting the interfacial bonding strength; it also could not effectively "anchor" the titanium dioxide particles firmly in the resin matrix, resulting in a decrease in its rubbing fastness. 3) Weather resistance: First, the titanium dioxide M-1 used in the color paste of the embodiment has a SiO2 coating layer. Under ultraviolet light irradiation, the lattice defects of titanium dioxide will generate electron-hole pairs, which will then generate hydroxyl radicals and superoxide anions. These strong oxidizing species will attack the resin molecular chains, leading to resin degradation, yellowing, and powdering. The SiO2 layer coating on the surface of titanium dioxide can isolate the active sites of titanium dioxide from direct contact with the resin, and can also capture the photogenerated electrons generated by titanium dioxide, inhibiting the generation of free radicals, thereby giving the color paste of the embodiment excellent weather resistance. In contrast, the titanium dioxide used in the color paste of Comparative Example 2 was not modified in any way, and its photocatalytic activity was fully exposed, resulting in a significant reduction in its weather resistance. The titanium dioxide M-C3 used in the color paste of Comparative Example 3 was only coated with a SiO2 layer and had no polymer layer. Although the SiO2 layer can partially inhibit photocatalysis, it has poor compatibility with the resin, and photo-oxidative degradation is still likely to occur at the interface, resulting in a reduction in its weather resistance. Furthermore, in the color pastes of the embodiments, both resin A-1 and titanium dioxide M-1 incorporate hyperbranched polyoxysilanes, exhibiting good compatibility. The high Si-O-Si bond energy in the hyperbranched structure makes the molecular chains less susceptible to UV damage, and the siloxane segments in the hyperbranched structure effectively absorb and scatter UV light. The resulting thick film forms a dense three-dimensional network, blocking UV and moisture penetration, thus giving the color paste excellent weather resistance. In contrast, the polymer grafting layer of titanium dioxide M-C4 used in the color paste of Comparative Example 4 does not contain hyperbranched polyoxysilanes, leading to a significant decrease in the color paste's weather resistance. Furthermore, the blocked isocyanate crosslinking agent contained in the pigment paste of the embodiment can form a three-dimensional chemical crosslinking network, which improves the density and crosslinking density of the pigment paste, delays the penetration of ultraviolet light and moisture, reduces the attack of free radicals on molecular chains, and effectively improves its weather resistance; while the pigment paste of Comparative Example 5 has no crosslinking agent, the crosslinking density of the pigment paste is low, and it is easy to generate microcracks, resulting in a decrease in its weather resistance. Furthermore, the anti-hydrolysis agent contained in the color paste of the embodiment can protect the stability of PPCD molecular chains in a humid and hot environment, thereby effectively ensuring the weather resistance of the color paste; while the color paste of Comparative Example 5 does not contain an anti-hydrolysis agent, and lacks the protective function of the anti-hydrolysis agent for resin A-1, resulting in a reduction in its weather resistance. 4) Heat and pressure resistance: First, the SiO2 layer in the modified titanium dioxide M-1 used in the color paste of the embodiment not only blocks the direct contact between titanium dioxide and resin, but also inhibits the high-temperature catalytic activity of titanium dioxide, thereby giving the color paste excellent heat-pressing resistance; while the titanium dioxide in the color paste of Comparative Example 2 has no SiO2 layer on its surface, resulting in a decrease in its heat-pressing resistance. Furthermore, the resin A-1 used in the color paste of the embodiment incorporates hyperbranched polyoxysilane. The high bond energy of the Si-O-Si bonds in the hyperbranched polyoxysilane structure endows the resin with excellent thermal stability, making it less prone to decomposition at 180°C. At the same time, the hyperbranched structure also has a low free volume and a high glass transition temperature, making it less prone to flow and deformation during hot pressing, thus resulting in excellent hot pressing resistance of the color paste. In contrast, the resin A-C1 used in the color paste of Comparative Example 1 does not contain a hyperbranched polyoxysilane structure, resulting in reduced hot pressing resistance. Furthermore, the color paste in the embodiment contains a crosslinking agent and an anti-hydrolysis agent. The crosslinking network formed by the crosslinking agent improves the cohesive strength and heat resistance of the color paste, and can resist cracking and adhesion reduction caused by thermal stress during hot pressing. The anti-hydrolysis agent can effectively ensure the stability of the resin structure, thereby giving the color paste excellent heat pressing resistance. In contrast, the color paste in Comparative Example 5 does not contain a crosslinking agent and an anti-hydrolysis agent, resulting in a decrease in its heat pressing resistance.

[0036] In summary, the film-forming resin used in the embodiments of the present invention is a hyperbranched polyoxysilane-modified carbon dioxide-based polyurethane acrylic hybrid resin, and the pigment used is modified titanium dioxide that has been sequentially modified with silica, silane coupling agent and polymer. The film-forming resin and the modified titanium dioxide have excellent compatibility. It also contains an adhesion promoter, crosslinking agent and anti-hydrolysis agent additive system. The components in the color paste have excellent synergistic effects, so the color paste of the embodiments has better weather resistance, rubbing fastness, adhesion and heat-pressing resistance than the color paste of the comparative example. It has excellent comprehensive performance and can be used as a white ink color paste for wood grain paper.

[0037] Finally, it should be noted that the above are only some preferred embodiments of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention shall fall within the scope of protection of the present invention.

Claims

1. A super weather-resistant wood grain paper white ink paste, characterized in that, It has the following composition and proportions: Modified polyurethane acrylic hybrid resin: 40-50 parts by weight; Modified titanium dioxide: 15-25 parts by weight; Adhesion promoter: 0.5-1.0 parts by weight; Leveling agent: 0.2-0.4 parts by weight; Ultraviolet absorber: 1.0-2.0 parts by weight; Hindered amine light stabilizer: 1.0-2.0 parts by weight; Crosslinking agent: 3-5 parts by weight; Anti-hydrolysis agent: 0.5-1.0 parts by weight; Defoamer: 0.2-0.4 parts by weight; 1,3-Propanediol: 5-8 parts by weight; Deionized water: 35-45 parts by weight; The modified polyurethane acrylate hybrid resin is obtained by first reacting polypropylene carbonate diol, isophorone diisocyanate, dimethylolpropionic acid and hydroxypropyl acrylate to obtain a polyurethane prepolymer, and then copolymerizing the polyurethane prepolymer with methyl methacrylate, butyl acrylate, isobornyl acrylate and hyperbranched polyoxysilane. The modified titanium dioxide is first coated with a silicon dioxide layer to obtain SiO2@TiO2 particles, and then the SiO2@TiO2 particles are surface activated using a silane coupling agent to obtain activated SiO2@TiO2 particles. Then, hyperbranched polyoxysilane, methyl methacrylate, and butyl acrylate are grafted and copolymerized onto the surface of the activated SiO2@TiO2 particles to form a copolymer layer. The hyperbranched polyoxysilane is obtained by the co-hydrolysis and polycondensation reaction of γ-glycidoxypropyltrimethoxysilane, γ-methacryloyloxypropyltrimethoxysilane and diethylene glycol; The preparation of the modified titanium dioxide includes the following steps: ①Preparation of SiO2@TiO2 particles: Disperse rutile titanium dioxide in deionized water, add sodium hexametaphosphate, adjust the pH to 9.0-10.0 with NaOH aqueous solution, then heat to 85-95℃, slowly add sodium silicate aqueous solution, and simultaneously add dilute sulfuric acid to maintain pH=9.0-10.0, with a adding time of 1.5-2 hours. After the adding is completed, keep warm for aging for 1-3 hours, filter, wash, and dry to obtain SiO2@TiO2 particles; ② Surface activation: Disperse SiO2@TiO2 particles in an ethanol aqueous solution, adjust the pH to 4-5 with glacial acetic acid, add silane coupling agent, react at 60-70℃ for 2-3 hours, filter, wash and dry to obtain activated SiO2@TiO2 particles; ③Graft copolymerization: Activated SiO2@TiO2 particles are dispersed in an appropriate amount of ethanol aqueous solution, hyperbranched polyoxysilane, methyl methacrylate, butyl acrylate and initiator are added, and the reaction is carried out at 75-80℃ under nitrogen protection for 3-5 hours. After filtration, washing and drying, the particles are pulverized and sieved to obtain modified titanium dioxide.

2. The ultra-weather-resistant wood grain paper white ink paste according to claim 1, characterized in that, In the modified polyurethane acrylic hybrid resin, the mass ratio of polypropylene carbonate diol: isophorone diisocyanate: dimethylolpropionic acid: hydroxypropyl acrylate: methyl methacrylate: butyl acrylate: isobornyl acrylate: hyperbranched polyoxysilane is 20-25: 8-12: 1-2: 2-3: 12-18: 6-10: 3-6: 2-4.

3. The ultra-weather-resistant wood grain paper white ink paste according to claim 2, characterized in that, The preparation of the modified polyurethane-acrylic hybrid resin includes the following steps: 1) Add polypropylene carbonate diol, isophorone diisocyanate, dimethylolpropionic acid and catalyst to a reactor and react at 85-90℃ for 2-3 hours under nitrogen protection; then cool to 60℃ and add hydroxypropyl acrylate for end-capping for 1.5-2 hours; then cool to 40℃ and add an appropriate amount of triethylamine to neutralize to pH=7.0-8.0; then add deionized water under high-speed stirring and emulsify for 20-30 minutes to obtain polyurethane prepolymer emulsion; 2) Heat the polyurethane prepolymer emulsion to 75-80℃, and under nitrogen protection, slowly add a mixture consisting of methyl methacrylate, butyl acrylate, isobornyl acrylate, hyperbranched polyoxysilane and initiator. The addition time is 2-3 hours. After the addition is completed, continue to keep the temperature for 2-3 hours to obtain the modified polyurethane acrylic hybrid resin.

4. The ultra-weather-resistant wood grain paper white ink paste according to claim 1, characterized in that, In step ①, the mass ratio of titanium dioxide: sodium hexametaphosphate: sodium silicate is 100:0.2-0.5:20-30.

5. The ultra-weather-resistant wood grain paper white ink paste according to claim 1, characterized in that, In step ②, the mass ratio of SiO2@TiO2 particles to silane coupling agent is 100:2-5, and the silane coupling agent is KH-570.

6. The ultra-weather-resistant wood grain paper white ink paste according to claim 1, characterized in that, In step ③, the mass ratio of activated SiO2@TiO2 particles: hyperbranched polyoxysilane: methyl methacrylate: butyl acrylate: initiator is 100:3-8:5-10:3-5:0.1-0.3; the initiator is azobisisobutyronitrile.

7. The ultra-weather-resistant wood grain paper white ink paste according to claim 1, characterized in that, In hyperbranched polyoxysilanes, the mass ratio of γ-glycidoxypropyltrimethoxysilane:γ-methacryloyloxypropyltrimethoxysilane:diethylene glycol is 22-28:12-20:10-18.

8. The ultra-weather-resistant wood grain paper white ink paste according to claim 7, characterized in that, The preparation of the hyperbranched polyoxysilane includes the following steps: γ-glycidoxypropyltrimethoxysilane, γ-methacryloyloxypropyltrimethoxysilane, diethylene glycol, ethanol and water were mixed, and the pH was adjusted to 3-4 with dilute hydrochloric acid. The mixture was hydrolyzed at 50-60℃ for 0.5-1.5 hours. Then the temperature was raised to 75-85℃ and the polycondensation reaction was carried out for 3-4 hours. After the reaction was completed, the mixture was distilled under reduced pressure to obtain hyperbranched polyoxysilane.

9. A method for preparing the ultra-weather-resistant wood grain paper white ink paste according to claim 1, characterized in that, Includes the following steps: a) Mix deionized water, 1,3-propanediol, adhesion promoter, leveling agent, defoamer, UV absorber, and hindered amine light stabilizer evenly. b) Add modified titanium dioxide and stir to mix evenly. Add the resulting mixture to a grinder and use zirconium dioxide as the grinding media to grind the mixture. After grinding, separate the resulting grinding solution from the zirconium beads. c) Add the modified polyurethane-acrylic hybrid resin and stir until it is evenly mixed; then add the crosslinking agent and anti-hydrolysis agent, stir until it is evenly mixed, filter and discharge to obtain the ultra-weather-resistant wood grain paper white ink paste.

Citation Information

Patent Citations

  • Preparation method of color paste for automobile color-changing film

    CN121086593A

  • Color paste for leather printing and preparation method thereof

    CN121611000A